Improving the Ability to Describe Plant Characteristics Through Project-Based Learning (PjBL) Method and Electronic Media - Huda, Miftahul (Universitas Sebelas Maret, 2022)
Education, in essence, is a conscious effort made by humans to develop their abilities and personalities. In the teaching and learning act4ities at SD Negeri 2 Bugel, it is evident that the learning outcomes of students are low, and they have not yet reached the passing grade (KKM), specifically 12 students, 7 students or 58% who have not achieved proficiency. The author str4es to address this issue through the improvement of learning by implementing the Project-Based Learning (PjBL) method as an effort to enhance the learning abilities of fourth-grade students in describing the specific characteristics of plants using electronic media at SD Negeri 2 Bugel. The research problem in this study is